Outlook on bismuth-based photocatalysts for environmental applications: A specific emphasis on Z-scheme mechanisms. (September 2022) - Balakumar, Srinivasan; Mahesh, Narayanan; Kamaraj, M.; Shyamalagowri, S.; Manjunathan, J.; Murugesan, S.; Aravind, J.; Babu, P. Suresh
Abstract: Semiconductor photocatalysis is thought to be a viable solution for addressing the growing problem of environmental pollution. Bismuth (Bi) metal oxides can function as a direct plasmonic photocatalyst or cocatalyst to accelerate the photogenerated charge separation and thus improve their photocatalytic activity. Hence, Bi-based photocatalysts have received a lot of attention due to their extensive environmental applications, including pollutant remediation and energy concepts. Massive efforts have been undertaken in the recent decade to find superior Bi-metal oxides (Bi2 XO6, X = MO, W, or Cr) and to uncover the corresponding photocatalytic reaction mechanism for the degradation of organic contaminants in water. Herein, the unique crystalline and electronic properties and main synthesis methods, as well as the major Bi-Based direct Z-scheme photocatalysts, are timely discussed and summarized in their usage in water treatment. Besides, the impact of Bi2 XO6 in energy storage devices and solar energy conversion is reviewed as an energy application. Finally, the future development and challenges of Z-scheme-based Bi2 XO6 photocatalysts are briefly explored, summarized, and forecasted. Graphical abstract: Image 1 Highlights: Bismuth based photocatalysis is a viable solution for addressing environmental pollution. Bismuth (Bi) metal oxides can function as a versatile photocatalyst. This review focus Bi-Z-Scheme application for aquatic environment. The impact of Bi2 XO6 in energy storage devices and solar energy conversion is also reviewed.